Becoming a queen - Clay, Dan, 1984- (Roaring Brook Press, 2023)
Reeling from a family tragedy, seventeen-year-old Mark finds his escape in a purple, sequenced, puff-sleeved princess dress, which becomes an unexpected outlet for his grief as well as a path towards love and self-expression.